2023
DOI: 10.3390/ijms24076598
|View full text |Cite
|
Sign up to set email alerts
|

Δ8-THC Protects against Amyloid Beta Toxicity Modulating ER Stress In Vitro: A Transcriptomic Analysis

Abstract: Alzheimer’s disease (AD) represents the most common form of dementia, characterized by amyloid β (Aβ) plaques and neurofibrillary tangles (NFTs). It is characterized by neuroinflammation, the accumulation of misfolded protein, ER stress and neuronal apoptosis. It is of main importance to find new therapeutic strategies because AD prevalence is increasing worldwide. Cannabinoids are arising as promising neuroprotective phytocompounds. In this study, we evaluated the neuroprotective potential of Δ8-THC pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…A growing body of studies have indicated that apoptotic cell death plays a critical role in the progression of neurodegenerative diseases [4,5]. The two main apoptotic pathways are the extrinsic pathway, which is initiated by a death ligand binding to a death receptor at the cell membrane, and the intrinsic pathway, which is triggered by the permeabilization of the mitochondrial outer membrane that leads to the release of mitochondrial proteins including cytochrome c and other apoptogenic factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of studies have indicated that apoptotic cell death plays a critical role in the progression of neurodegenerative diseases [4,5]. The two main apoptotic pathways are the extrinsic pathway, which is initiated by a death ligand binding to a death receptor at the cell membrane, and the intrinsic pathway, which is triggered by the permeabilization of the mitochondrial outer membrane that leads to the release of mitochondrial proteins including cytochrome c and other apoptogenic factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the dose was based on previous studies. Indeed, in other previous experiments, we observed no cytotoxicity and the dose of 20 µM Δ 8 -THC was more suitable to reveal its effects [ 17 ].…”
Section: Discussionmentioning
confidence: 89%
“…In order to obtain 182 mg (yield 91%) of Δ 8 -THC (1) as a brown oil, the residue underwent purification by Gravity Column Chromatography (GCC) on silica gel (pure petroleum ether to petroleum ether-EtOAc 9:1). A further step of purification was performed using JASCO Hichrom, 250 × 25 mm, silica UV−vis detector-2075 plus (silica, petroleum-ether-EtOAc gradient from 95:5 to 85:15), obtaining 150 mg of Δ 8 -THC (99% purity) as a brownish powder, whose structure has been identified in accordance with proton nuclear magnetic resonance ( 1 H NMR) [ 17 ], using Bruker 400 spectrometers (Bruker ® , Billerica, MA, USA), and the results were previously demonstrated [ 23 ]. The residues of solvent were identified as responsible for the chemical shifts (CDCl 3 : δH = 7.26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THC has not been shown to reduce proinflammatory cytokine levels or to increase anti-inflammatory cytokines in models of neurological diseases, although significant improvements in neuropathic pain have been reported [75,103,104]. However, THC has recently been proposed as a new neuroprotective agent in Alzheimer's disease due to its ability to restore cell viability in retinoic acid-differentiated neuroblastoma SH-SY5Y cells and upregulate genes involved in endoplasmic reticulum stress and the unfolded protein response [105]. Additionally, it was demonstrated that THC (5 mg) combined with codeine (50 mg) exhibited analgesic and antispastic effects in a patient with spasticity and pain due to spinal cord injury [106].…”
Section: Role Of Cannabis Compounds In Neurological and Systemic Infl...mentioning
confidence: 99%